New Hosts of Simplicimonas similis and Trichomitus batrachorum Identified by 18S Ribosomal RNA Gene Sequences. (10th July 2013) - Dimasuay, Kris Genelyn B.; Lavilla, Orlie John Y.; Rivera, Windell L.
Abstract : Trichomonads are obligate anaerobes generally found in the digestive and genitourinary tract of domestic animals. In this study, four trichomonad isolates were obtained from carabao, dog, and pig hosts using rectal swab. Genomic DNA was extracted using Chelex method and the 18S rRNA gene was successfully amplified through novel sets of primers and undergone DNA sequencing. Aligned isolate sequences together with retrieved 18S rRNA gene sequences of known trichomonads were utilized to generate phylogenetic trees using maximum likelihood and neighbor-joining analyses. Two isolates from carabao were identified as Simplicimonas similis while each isolate from dog and pig was identified as Pentatrichomonas hominis and Trichomitus batrachorum, respectively. This is the first report of S. similis in carabao and the identification of T. batrachorum in pig using 18S rRNA gene sequence analysis. The generated phylogenetic tree yielded three distinct groups mostly with relatively moderate to high bootstrap support and in agreement with the most recent classification. Pathogenic potential of the trichomonads in these hosts still needs further investigation.